Augmented reality network : a collaborative augmented reality desktop game - Tiong, Amy Siaw Wei (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Augmented Reality (AR) is a technology that augments virtual objects in the real environment. The users can see and interact with the virtual objects. AR can enhance the real world with the virtual infonnation and increase the productivity of our daily life. Collaborative AR provides a shared space to the users and allows the users to solve problems together. Through this research, a collaborative AR · system called AR Network was designed and developed. AR Network allows the users to playa game collaboratively) The game developed for AR Network is called SameGame. SameGame was used to represent a problem which the users can solve collaboratively. This indicates that AR Network has the possibilities to be implemented in other fields such as education and entertainment. In order to implement an AR Network, Transmission Control Protocol (TCP)lIntemet Protocol (IP) suite was used to transfer data in the network. Client-server architecture was used in this research so that the data can be stored in the server and transferred to the clients. Vision-based tracking was used for AR registration. Fiduciary markers were required to compute the orientation and the position ofthe camera so that the computer generated objects .were correctly placed in the real world. AR Network was evaluated for its functionality and its perfonnance. AR Network allowed more than two participants to solve a puzzle collaboratively. The results also showed that the participants had positive perception towards collaboration in AR Network.